PERANAN CIVIC COMMUNITY DALAM MENDORONG PEMUDA SEBAGAI PELOPOR KEMANDIRIAN BANGSA (Studi kasus pada komunitas “Pasukan Kresek” di Kabupaten Malang Jawa Timur) - Mawarti, Rista Ayu; Sundawa, Dadang (Nurani, 2016)
The role of civic community in encouraging the youth as the pioneer of the nation self- reliance. This study aims to explore the role of civic community in optimising the potential of youth in order to become the pioneer of nation self-reliance. The research method used, i.e. qualitative approach to the design of case studies on community "Pasukan Kresek"  in Malang Regency, East Java. The results showed  that "Pasukan Kresek" as a civic community serves as a media that enable the youth participation through social movements  which based on self-reliance and local things oriented to create the better future. Thus, it could raise the greatest potentials of the youth as the pioneer of the nation self-reliance.